To study the compressive strength of solid timber column / Norhana Sabawas - Sabawas, Norhana (1993)
The Modulus of Elasticity of timber is an important application in structural timber design calculations in estimating the deflection of flexural members and as parameter in calculating the buckling strength of limber members. This study emphasize on the realistic value of Modulus of Elasticity of limber columns configuration. To obtain the closest deflection of the timber columns at selected pointe on the samples tested, the ANSYS program is utilised to iterate the value of Modulus of Elasticity of the timber column-Predetermined testing was carried out at it timber member (timber column). The discrepancies of the Modulus of Elasticity of timber member obtained from the iteration with value obtain using ASTM,D: 143 (method of small clear specimen) are elaborated herein.